PENINGKATAN KINERJA BERBASIS PARTISIPASI DALAM PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI DAN PENGARUHNYA TERHADAP KESENJANGAN ANGGARAN - ., Amin Wahyudi (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2008)
Abstract The organization require budget to translate the overall of strategy into target and plan short-range and is long-range (Mowen and Hansen, 1997: 76). To guarantee to made by decision is top management do not digress from executed activity by all manager, needed by activity of operation. The despitefully needed by good communications between manager culminate with all middle storey; level manager and under, so that all manager feel to involve in stipulating of budget. Participation in compilation of budget can improve organizational effectiveness through the make-up of manager performance (Indriantoro and Supomo, 1998: 55). Participation in this case is taking part in taker part. Manager participation in compilation of budget expected can give motivation to manager in executing its responsibility. Participation represent one of the effective management technique because all manager can accept and execute fully responsibility to the budget which have been compiled, so that compiled budget participationly become is realistic. Keywords: participation budget, organizational komitmen, difference budget